Dilemma of dihydropyrimidine dehydrogenase deficiency in colorectal cancer patients: is Uftoral® the right answer?. (August 2014) - Rastogi, Sameer; Sirohi, Bhawna; Deodhar, Kedar; Shetty, Nitin; Shrikhande, Shailesh V
SUMMARY : Fluoropyrimidines (5-fluorouracil, capecitabine, S-1, Uftoral ® [UFT; Merck, Germany]) and their derivatives are effective in management of colorectal cancer. DPD deficiency is not routinely tested and is usually diagnosed after a patient has severe/grade IV toxicity secondary to the use of 5-fluorouracil or capecitabine. Once DPD deficiency is diagnosed, there are sparse data on the use of UFT or raltitrexed and there are no comparable outcome data with well-known regimens like infusional 5-fluorouracil, leucovorin oxaliplatin (FOLFOX) and infusional 5-fluorouracil, leucovorin, irinotecan (FOLFIRI). Here we report the first case series from India of DPD deficiency and the use of UFT.